PERLINDUNGAN HUKUM NASABAH DALAM PENYELENGGARAN LAYANAN PERBANKAN DIGITAL - Tarantang, Jefry; Syawaliah, Syawaliah; Astiti, Ni Nyoman Adi; Kasenda, Dekie G.G. (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Bank customer protection is designed to give customers the right to complain and resolve disputes in the banking industry. Customer protection laws and regulations in the banking industry are not good at protecting customers. Changes in services using information technology paved the way for the digital banking era. However, the spread of digital banking services also increases bank risk. The purpose of this research is to elaborate on legal protection in the development of digital banking services and protect the public from risks. Digital banking services are innovations made by banks to meet the needs of customers who are still developing their information technology. In Indonesia, the introduction of digital banking services offered by banks is regulated in OJK Regulation 12/POJK.03/2018 concerning the Introduction of Digital Banking Services in Commercial Goods Banking Services. Customers who use digital banking services have two forms of protection, namely prevention and protection.